Investigating the In Vivo Expression Patterns of miR-7 microRNA Family Members in the Adult Mouse Brain - A. Sanek, Nicholas; Scott Young, W. (MicroRNA, 2012)
MicroRNAs (miRNAs) are endogenous non-coding RNAs that play critical roles in regulating transcription in eukaryotes. miRNAs are involved in a wide-range of biological processes. Because miRNA research is relatively new, it is not surprising that tools and techniques to study their biology are still being developed. Our laboratory is interested in carefully delineating the in vivo expression patterns between three closely related miR-7 miRNA family members in the mouse. The miR-7 family of miRNAs is conserved between humans and invertebrates. The miR-7 family also shows conserved expression in neural tissues, and members of this family are involved in the development of sensory structures in flies, associated with many types of cancer, and likely play a role in osmoregulation in the mouse brain. In this study, we used multiple methods to differentiate the expression of the miR-7 family members in the mouse brain. Our results suggest that although there are useful tools for exploring miRNA expression in vivo, better tools and/or methods are still needed for thorough in vivo studies of closely related family members.
Keywords: hybridization